Reduced FEV1 as Prognostic Factors in Patients With Advanced NSCLC Receiving Immune Checkpoint Inhibitors - Shen, Yi-Luen; Shen, Chia-I; Chiang, Chi-Lu; Huang, Hsu-Ching; Chou, Kun-Ta; Chiu, Chao-Hua; Chen, Yuh-Min; Luo, Yung-Hung (Frontiers in Medicine, 2022)
Background: The aim of study is to investigate the influence of pulmonary function on the prognosis in patients with advanced non-small cell lung cancer (NSCLC) receiving immune checkpoint inhibitors (ICI). Patients and Methods: Data were collected retrospectively from 151 patients with stage IV NSCLC who received ICI and completed spirometry before ICI therapy in Taipei Veterans General Hospital between January 2016 and December 2020. The co-primary end points were overall survival (OS) and progression-free survival (PFS) between groups divided by 80% predicted FEV1 since ICI therapy started; the secondary outcomes were objective response rate. Results: Among 151 patients enrolled to this study, 67.5% of patients were men, 75.5% were adenocarcinoma, 24.5% had known targetable driver mutation, 33.8% received first-line ICI, and 62.8% received ICI monotherapy. The objective response rate was 24.5% and disease control rate was 54.3%. In multivariable analysis, patient with reduced FEV1 had inferior PFS (FEV1<80% vs. FEV1≥80%, adjusted HR=1.80, P=0.006) and OS (FEV1<80% vs. FEV1≥80%, adjusted HR=2.50, P<0.001). Median PFS and OS in the preserved FEV1 group (≥80% predicted FEV1) compared to the reduced FEV1 group (<80% predicted FEV1) were 5.4 vs. 2.9 months (HR=1.76, P=0.003) and 34.9 vs. 11.1 months (HR=2.44, P<0.001), respectively. The other independent prognostic factors of OS include stage IVA disease (adjusted HR=0.57, P=0.037), initial liver metastasis (adjusted HR=2.00, P=0.049), ICI monotherapy (adjusted HR=1.73, P=0.042) and ICI related pneumonitis (adjusted HR=3.44, P=0.025). Conclusions: Reduced FEV1 is strongly associated with inferior clinical outcomes in patients with advanced NSCLC treated with ICI.